Environmental and biological requirements of post-smolt Atlantic salmon (Salmo salar L.) in closed-containment aquaculture systems - Calabrese, Sara (Aquaculture, 2017)
Production of Atlantic salmon (Salmo salar L.), exceeds 2 million tonnes globally, and accounts for 90% of the salmon on the market. Presently, the predominant production of post-smolt Atlantic salmon occurs in open sea cages. Environmental concerns, during the production phase at sea are limiting further growth of the industry. In closed-containment aquaculture systems (CCS), the cultured fish are separated from the natural environment by a physical barrier; these can be land-based systems or closed units in the sea. Using CCS to shorten the time fish are reared in open sea cages has been highlighted as key to solving important challenges the industry is facing today. However, there is a lack of knowledge on the biological and environmental requirements of post-smolt Atlantic salmon in CCS. This thesis aims to provide insight on the effects of some key husbandry conditions on post-smolt performance and welfare in both seaand land-based CCS. Commercial feasibility of farming post-smolt Atlantic salmon in CCS in the sea relies on maximizing fish density. To assess stocking density limits, five different densities (25, 50, 75, 100 and 125 kg m-3) were maintained in flow-through seawater systems for eight weeks. Increased stocking density had a negative effect on growth and feed utilization, and increasing density from 100 kg m-3 to 125 kg m-3 lead to a 42 % decrease in growth rate. After eight weeks, primary (elevated plasma cortisol) and secondary (hydro-mineral and acid-base) stress responses were observed in the highest density treatment compared to other treatments. Densities of 100 kg m-3 or more also increased pectoral fin damage and cataracts. Fish stocked at the medium (75 kg m-3) density displayed more robust telencephalic activation of both stress and neural plasticity responses, compared to fish in the lowest (25 kg m-3) and highest (125 kg m-3) densities. Overall, the results suggest that stocking density can be maximized up 75 kg m-3 without compromising performance and welfare in Atlantic salmon ...